The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1051/matecconf/201824602033
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic grey early warning model for dam deformation based on wavelet denoising

Abstract: Influenced by environment and human factors, the observed data of dam deformation consist of real deformation value and observation error (noise). The conventional GM(1,1) model based on nondenoised observation data is not very effective. In order to improve the prediction effect of conventional GM(1,1) model, wavelet threshold denoising method is used to eliminate the noise in the original data and improve the smoothness of the data sequence. Then, based on the conventional GM(1,1) model, the metabolic GM(1,1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…n i=k+1 (7) CMSE criterion is to find the kth IMF, so as to determine that the first k highfrequency IMFs are mainly noisy information. This method has the advantages of simple calculation and strong adaptive, and does not need to set the threshold manually.…”
Section: T (T)=mentioning
confidence: 99%
See 1 more Smart Citation
“…n i=k+1 (7) CMSE criterion is to find the kth IMF, so as to determine that the first k highfrequency IMFs are mainly noisy information. This method has the advantages of simple calculation and strong adaptive, and does not need to set the threshold manually.…”
Section: T (T)=mentioning
confidence: 99%
“…It has been widely used in data noise reduction, signal analysis, image processing and other fields [5,6]. Wu [7] added wavelet analysis to GM (1,1) model, and the results showed that wavelet threshold denoising can obviously remove the noise in original data. Li [8] also used wavelet analysis to denoise the dam deformation data, and then reconstructed the extracted comprehensive components to obtain a hybrid model to predict the dam deformation.…”
Section: Introductionmentioning
confidence: 99%
“…The traditional signal decomposition techniques mainly include Fourier transform, Wavelet Decomposition (WD) and Empirical Mode Decomposition (EMD) which are frequently applied to decompose the dam deformation sequence [24]. Fourier transform can realize the mutual conversion from time domain to frequency domain, while its conditions are relatively harsh, and there is no Fourier transform for considerable useful signals; WD has a certain priority, while it is difficult to choose the basis function and decomposition scale.…”
Section: Introductionmentioning
confidence: 99%